2021
DOI: 10.1111/eip.13138
|View full text |Cite
|
Sign up to set email alerts
|

Medication strategies in first episode psychosis patients: A survey among psychiatrists

Abstract: Aim: There is an ongoing debate regarding the optimal timing of discontinuation of antipsychotic drugs for patients with first episode psychosis. Although most guidelines recommend maintenance therapy for at least 1 or 2 years after reaching remission, study results indicate that early discontinuation may be beneficial for at least a subsample of patients. To date, little is known about which medication strategies are applied in patients recovering from a first psychotic episode. In this study, we examined the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 35 publications
(47 reference statements)
0
9
0
Order By: Relevance
“…Awaiting future results, the ongoing HAMLETT trial 4 investigated antipsychotic treatment practices among Dutch psychiatrists specialised in early psychosis; within the first year after remission, they already taper medication in 33•8% of patients having a first episode and discontinue medication in 9•1% of patients. 10 These findings might reflect the practice of shared-decision making, in which patients' preferences are an important factor in choosing treatment strategies, and the patients often have a strong wish to stop medication earlier and will do so on their own when not supported by their physician.…”
Section: Antipsychotic Maintenance Treatment Versus Dose Reduction: H...mentioning
confidence: 98%
“…Awaiting future results, the ongoing HAMLETT trial 4 investigated antipsychotic treatment practices among Dutch psychiatrists specialised in early psychosis; within the first year after remission, they already taper medication in 33•8% of patients having a first episode and discontinue medication in 9•1% of patients. 10 These findings might reflect the practice of shared-decision making, in which patients' preferences are an important factor in choosing treatment strategies, and the patients often have a strong wish to stop medication earlier and will do so on their own when not supported by their physician.…”
Section: Antipsychotic Maintenance Treatment Versus Dose Reduction: H...mentioning
confidence: 98%
“…Beauchamp and Childress (2019) explained that harm is a contested concept but includes “significant bodily harms and setbacks to other significant interests” (p. 1159). Thus, a key concern of many psychiatrists regarding antipsychotic tapering or discontinuation is the potential to cause harm by increasing the chance of symptom exacerbation or psychotic relapse (Kikkert et al, 2022; Moncrieff et al, 2020). Few clinicians also believe that a person may experience poorer personal, social, and vocational functioning if medication is discontinued (Kikkert et al, 2022).…”
Section: Nonmaleficence and Beneficencementioning
confidence: 99%
“…A recent study showed that the mean time to medication nonadherence following a first-episode of psychosis is 10 months (Daneault et al, 2019). Clinicians report being somewhat supportive of antipsychotic dose reduction (Cooper et al, 2019; Murray et al, 2016), and psychiatrists commonly commence dose reduction within months of remission following a first-episode psychosis in accordance with patient wishes (Kikkert et al, 2022). Thus, there is some tension between clinical practice guidelines and real-world preferences and practices (A.…”
mentioning
confidence: 99%
“…Knowledge of reasons to discontinue or continue antipsychotics is valuable to individuals with first‐episode schizophrenia, their relatives, and clinicians. Furthermore, identifying factors associated with discontinuation and continuation is helpful for the patient and clinician in the process of shared decision‐making, increasing adherence, and helping with a safe reduction of antipsychotics (Kikkert et al, 2022). However, studies of self‐reported reasons in individuals with first‐episode schizophrenia are sparse (Wade et al, 2017), and risk factors for discontinuation are described in a few studies (Ljungdalh, 2017; Sendt et al, 2015).…”
Section: Introductionmentioning
confidence: 99%